THE EFFECT OF USING DIRECT METHOD IN TEACHING SPEAKING SKILL AT THE SECOND YEAR OF SMK NEGERI 1 BENER MERIAH-ACEH - Umar Haliwanda (Universitas Putera Batam, 2019)
This study aims at investigating at the use of Direct Method in the classroom, a few of English teacher applied many strategies and methods to increase students’ speaking skill throughout describing and asking responses from the students, sometimes the teacher using group discussion, role play/simulation, picture story, and game, etc. . Besides, using interesting strategies or methods. But in reality, the students faced the problem, while the researcher using Direct Method in this study the students able to speak each other. Subsequently has improvement in speaking skill. The main focused in this study is to know the effect using Direct Method before and after being taught by using Direct Method. And also emphasizes the benefits of the Direct Method to teach how to communicate in the target language.